2000
DOI: 10.1103/physreva.62.012706
|View full text |Cite
|
Sign up to set email alerts
|

Dichroism in the electron-impact ionization of excited and oriented sodium atoms

Abstract: Measurements are reported for kinematically complete electron-impact ionization collisions with oriented 3 P sodium atoms excited from the ground state by right-and left-hand circularly polarized light. The measurements reveal a strong dependence of the ionization cross section on the helicity inversion of the exciting photon. This dichroic effect and the magnetic state resolved cross sections are described using the distortedwave Born approximation and the dynamically screened Coulomb wave method. Within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Indeed the technology used in these experiments has evolved to the point where the spin of the electrons involved in the ionization process can also be determined. Recent coincidence measurements of electron-impact ionization of lithium and sodium employed spin-polarized electrons in a coplanar asymmetric geometry [3,4], and the results have offered a particular challenge to theorists. In Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed the technology used in these experiments has evolved to the point where the spin of the electrons involved in the ionization process can also be determined. Recent coincidence measurements of electron-impact ionization of lithium and sodium employed spin-polarized electrons in a coplanar asymmetric geometry [3,4], and the results have offered a particular challenge to theorists. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…[3] the experimental data were compared with two of the most sophisticated theoretical models available, the convergent close-coupling (CCC) method and the distorted-wave Born approximation (DWBA). Lower et al [4] considered two approximations, the DWBA and the dynamically screened three-Coulomb-wave method. The comparison of theory and experiment showed varying levels of agreement with the different theoretical approximations, depending upon the kinematical regime under investigation, and the results clearly indicated that the most stringent test of the theories occurs for low incident and outgoing electron energies.…”
Section: Introductionmentioning
confidence: 99%
“…For metallic target species, a recirculating metal-vapor oven is employed. 53 In this case, atoms effuse through a 1 mm diameter circular aperture, with the atomic beam constrained to the x-y scattering plane and directed towards the z axis. For those experiments in which laserpumped excited and/or oriented atomic target states are of interest, a second laser system is employed comprising a Coherent CR-699-21 ring dye laser pumped by a Coherent Innova 300 argon ion laser.…”
Section: The Anu "E 2e… Spectrometermentioning
confidence: 99%
“…The spin polarization of the target ensemble and its angular-momentum orientation 54 ͑each either into, or out of the scattering plane͒ are controlled by the reversing the helicity of dye laser light through the actions of a linear polarizer and 1 4 -wave retarder introduced between the dye laser and the interaction region. 53 Electrons scattered within the x-y plane are momentum analyzed in one of the two double-toroidal-sector electrostatic energy analyzers, one located on each side of the primary electron beam. Measurements are restricted to ͑e ,2e͒ events falling within the angular and energy acceptance ranges of the two toroidal analyzers, namely, 285°ഛ 1 ഛ 355°, 5°ഛ 2 ഛ 135°, ⌬E 1 = E 1 ± 0.1E 0 , and ⌬E 2 = E 2 ± 0.1E 0 .…”
Section: The Anu "E 2e… Spectrometermentioning
confidence: 99%
“…This study unravels two novel independent features when a polarized electron beam ionizes an oriented target, namely, a quantity that depends on the polarization of the incoming electron beam but not on the helicity of the exciting photon used to orient the target and an observable that resembles the spin asymmetry A s but differs markedly in behavior due to the presence of orbital orientation. Figure 1 shows schematically the experimental and kinematical arrangement described in detail in a previous publication [9]. A collimated target beam of sodium atoms is produced by effusion through a 1 mm diameter exit nozzle of an Ohmically heated recirculating sodium oven.…”
mentioning
confidence: 99%